Numerical study of passive thermal management for a high-temperature, high-speed rotary joint using an internal air gap - Kim, Jeong-Hwa; Choi, Byung-Hyun (Frontiers in Mechanical Engineering, 2025)
Excessive axial heat transfer through the shaft of high-speed rotary systems exposed to hot fluids can cause bearing overheating, lubricant degradation, thermal expansion-induced interference, and premature failure. This study introduces a passive thermal insulation strategy by incorporating an internal air gap within the shaft to disrupt the conduction path. Two rotary joint configurations—a conventional solid shaft and a modified shaft with an air gap—were evaluated under identical conditions using steady-state CFD simulations in ANSYS Fluent. The air-gap design lowered the peak bearing temperature by approximately 55%, a reduction attributed to increased thermal resistance and natural convection within the gap. A one-dimensional thermal resistance model further validated these findings, showing strong agreement with the CFD predictions. These results demonstrate that bearing overheating can be effectively mitigated without the need for surface coatings or external cooling systems, highlighting a simple yet robust design alternative for thermal management in next-generation high-temperature, high-speed rotary machinery.